2012
DOI: 10.2399/prn.12.0202007
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Heterotopic Pregnancy in a Spontaneous Cycle

Abstract: Objective: Heterotopic pregnancy is a condition in which extrauterine and intrauterine pregnancy coincides. It is encountered very rarely especially in the absence of risk factors. The incidence of heterotopic pregnancy has increased in recent years due to the developments in assisted reproductive technologies (ART). In this case report, we aimed to emphasize the early diagnosis and proper management of heterotopic pregnancies with its mortality and morbidity rates and importance for future fertility. Case: Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It has been suggested that a delay in diagnosis can cause maternal mortality of 1% and foetal mortality of 45-65% [2]. It is important to perform a meticulous pelvic sonography evaluation to detect HP even in cases with a positive pregnancy test and an intrauterine gestational sac on sonography after infertility treatment [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that a delay in diagnosis can cause maternal mortality of 1% and foetal mortality of 45-65% [2]. It is important to perform a meticulous pelvic sonography evaluation to detect HP even in cases with a positive pregnancy test and an intrauterine gestational sac on sonography after infertility treatment [1].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of a HP can be challenging and a high index of suspicion is mandatory for early diagnosis and appropriate treatment. High-resolution TVUS is the primary diagnostic method in HP [2]. The findings of a complex cyst in the adnexal area, a haematosalpinx, a tubal ring and a foetal heart rate and free fluid in the Douglas space should raise the suspicion of a HP [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations